Digitalization of health care and aspects of implementing electronic prescriptions in Bulgaria - Atanas Toshev; Elina Petkova-Gueorguieva; Anna A. Mihaylova; Vidin Kirkov; Vasil G. Madzharov; Hristina Lebanova; Svetoslav Stoev; Stanislav Gueorguiev (Pensoft Publishers, 2024)
The digitization of health systems is a topic of immense significance for the modern world. It holds the potential to transform the delivery of healthcare services, enhancing their quality, efficiency, and accessibility. Electronic prescriptions are a key element of this process, but it is crucial to ensure their implementation protects patients' personal data and privacy. This article examines the digitization of health systems in Bulgaria, with a focus on electronic prescriptions. It highlights aspects of data protection, the potential risks associated with data misuse, and the advantages of electronic prescriptions.